استخدام مدخل قياس التكاليف للمحاسبة عن استهلاك الموارد "RCA" وسلسلة التوريد البيئية مع عمليات المصادر الخارجية "BPO" في دعم القدرة التنافسية لمنشآت الأعمال الصناعية: دراسة ميدانية - شكر، إيناس جمعة فهمي (جامعة بورسعيد - كلية التجارة, 2021)
هدف البحث إلى التعرف على مدي تطبيق أبعاد المحاسبة عن استهلاك الموارد (RCA) وإدارة تكاليف سلسلة التوريد البيئية - ومدى تأثيرهم على عمليات المصادر الخارجية (BPO) في الشركات الصناعية، وذلك من خلال بناء واقتراح إطار محاسبي يساعد في تحقيق العديد من المزايا الكبيرة والهامة التي يحققها هذا التكامل في تقديم معلومات حيوية تساعد الإدارة في تنفيذ العديد من الوظائف واتخاذ العديد من القرارات الإدارية تمهيداً لخفض تكاليف المنتجات إلى المستويات التنافسية، لتحقيق أهداف الدراسة حددت الباحثة مجتمع البحث شملت الإدارة العليا (المدير العام ورؤساء الأقسام والعاملين في قسم الجودة، والمتوسطة باعتبارهم الفئة المنوط بها البحث، وقد تم تحديد حجم العينة في حدود 170 شركة، وقد تم توزيع 120 استمارة عليهم. وتوصلت الدراسة إلى تم قبول الفرض الأول، وهو: "لا يوجد اختلافاً معنوياً حول دور مدخل المحاسبة عن استهلاك الموارد (RCA) وسلسلة التوريد البيئية مع عمليات المصادر الخارجية (BPO) في تحقيق ووفورات في تكاليف الشركات الصناعية"، وكذلك تم قبول الفرض الثاني، وهو: "لا يوجد اختلافا معنويا حول تطبيق المحاسبة عن استهلاك الموارد(RCA) وسلسلة التوريد البيئية مع عمليات المصادر الخارجية (BPO) إلى إعطاء الشركة القدرة على إنتاج منتجات متعددة تفي بمتطلبات العملاء، وتم قبول الفرض الثالث: وهو هناك تأثير جوهري ذو دلالة إحصائية بين تكامل نظام المحاسبة عن استهلاك الموارد (RCA) وسلسلة التوريد البيئية مع عمليات المصادر الخارجية (BPO) ودعم المركز التنافسي للشركات الصناعية.
The aim of the research is to identify the extent of the application of the dimensions of resource consumption accounting (RCA), environmental supply chain cost management - and the extent of their impact on the operations of external sources (BPO) in industrial companies, through building and proposing an accounting framework that helps in achieving many large and important advantages. In order for this integration to be achieved by providing vital information that helps the administration in the implementation of many functions and to take many administrative decisions in preparation for reducing the costs of products to competitive levels, to achieve the objectives of the study, the researcher identified the research community that included the senior management) the general manager, heads of departments and workers in the quality and medium department as The category entrusted with the research, and the sample size has been determined in the range of 170 companies, and 120 questionnaires have been distributed to them. The study concluded that the first hypothesis was accepted, which is: "There is no significant difference regarding the role of the Resource Consumption Accounting Approach (RCA) and the environmental supply chain with external source operations (BPO) in achieving savings in the costs of industrial companies". The second hypothesis was also accepted. It is: "There is no significant difference regarding the application of resource consumption accounting (RCA) and the environmental supply chain with external sourcing operations (BPO) to giving the company the ability to produce multiple products that meet customer requirements. The third hypothesis has been accepted: and there is a significant significant effect. A statistic between the integration of the Resource Consumption Accounting (RCA) system and the environmental supply chain with Outsourcing Operations (BPO) and the competitive position support for industrial firms
Keywords: الدراسات الاقتصادية -- إدارة التكاليف -- محاسبة استهلاك الموارد -- سلسلة التوريد البيئية -- مصر